Plexiform Ameloblastoma of the Mandible - Chauhan, Dinesh Singh; Guruprasad, Yadavalli
Ameloblastoma is a common and aggressive odontogenic epithelial tumor. It has an aggressive behavior and recurrent course, and is rarely metastatic. Ameloblastoma represents 1% of all tumors and cysts that involve the maxillomandibular area and about 10% of the odontogenic tumors. It is primarily seen in adults in the third to fifth decade of life, with equal sex predilection. Radiographically, it appears as an expansile radiolucent, with thinned and perforated cortices, and is known to cause root resorption. As it shares common radiographic features with other lesions such as the giant cell tumor, aneurismal bone cyst, and renal cell carcinoma metastasis, a definitive diagnosis can only be made with histopathology. We present an extensive case of plexiform ameloblastoma of the mandible in a 42-year-old female patient.